1997
DOI: 10.1039/a700738h
|View full text |Cite
|
Sign up to set email alerts
|

A novel method of preparing thiol-derivatised nanoparticles of gold, platinum and silver forming superstructures

Abstract: Fig. 3 TEM images of thiol-derivatised Pt (a) and Ag (b) nanoparticles 538

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(33 citation statements)
references
References 9 publications
1
32
0
Order By: Relevance
“…Electrochemical [162] as well as sonoelectrochemical [163] methods of syntheses also have been reported. A number of similar nanocrystal systems have been reported in the literature [164][165][166]. It is found that the Au/thiol system is thermodynamically stable while others are kinetically stable [164].…”
Section: Synthesismentioning
confidence: 84%
“…Electrochemical [162] as well as sonoelectrochemical [163] methods of syntheses also have been reported. A number of similar nanocrystal systems have been reported in the literature [164][165][166]. It is found that the Au/thiol system is thermodynamically stable while others are kinetically stable [164].…”
Section: Synthesismentioning
confidence: 84%
“…Nowadays, at least two basic ways of surface functionalization in relation to nanoparticles are possible: functionalization of the nanoparticle surface and modification of solid surfaces and matrices by nanoparticles. As first, surface modification of nanoparticles by incorporation of various ligands (Sakura et al 2005;Stenkamp et al 2001;Zhao et al 2005;Liu et al 2008), functional groups (Hiramatsu and Osterloh 2004;Sarathy et al 1997) and many others species (Wang et al 2002;Thompson et al 2008) onto nanoparticle surfaces is considered. This approach determines the interaction between modified nanoparticles, environment and biosystems as well as allows to control the growth of the particles and prevents their aggregation and precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of tert‐ docecanethiol‐coated gold and silver nanoparticles : Gold nanoparticles were prepared according to a literature procedure 40. Silver nanoparticles were prepared by a modified literature method 41. AgNO 3 (150 mg) was dissolved in water (7 mL), then tetraoctylammonium bromide (300 mg) in toluene (7 mL) was added with stirring.…”
Section: Methodsmentioning
confidence: 99%